Running from depression: a review of aerobic exercise as an adjunctive treatment for mood disorders - Adasik, Damian; Bonarska , Marta; Łocik, Gabriela; Szymczyk, Simone; Król, Kacper (Quality in Sport, 2025)
Background: Mood disorders, including major depressive disorder (MDD) and anxiety disorders, significantly impact global mental health, contributing to disability and reduced quality of life. While pharmacotherapy and psychotherapy are standard treatments, many patients experience residual symptoms or treatment resistance. Aerobic exercise has emerged as a promising adjunctive intervention due to its psychological and neurobiological benefits. This review examines its efficacy, mechanisms, optimal implementation strategies, and integration into psychiatric care. Methods: A narrative literature review was conducted using PubMed, Embase, and other relevant databases, focusing on studies published up to 2025. Keywords such as "aerobic exercise," "depression," "anxiety," "psychiatric disorders," and "neurobiological mechanisms" were used to identify studies assessing clinical outcomes, neurobiological effects, and adherence factors. Results: Aerobic exercise significantly reduces depression and anxiety symptoms across diverse populations, with moderate-to-large effect sizes in randomized controlled trials. Mechanistically, it enhances neurotransmitter balance, increases brain-derived neurotrophic factor (BDNF), regulates the hypothalamic-pituitary-adrenal (HPA) axis, and improves cognitive function. Optimal outcomes are observed with moderate-intensity exercise (60–80% HRmax), performed three times per week for at least 8–12 weeks. Supervised and group-based interventions improve adherence, particularly in psychiatric populations. Conclusions: Aerobic exercise represents a viable, low-cost, and effective adjunct to traditional psychiatric treatments. However, methodological limitations, lack of long-term data, and adherence challenges remain. Future research should focus on standardized protocols, personalized exercise prescriptions, and large-scale, multi-center trials to maximize clinical integration and optimize patient outcomes.